Effects of the Fenton reagent on transport in yeast - Khansuwan, U; Kotyk, A (Folia microbiologica, 2000)
In the facultatively anaerobic yeast Saccharomyces cerevisiae the uptake rate and the accumulation ratio of 2-aminoisobutyric acid was decreased by some 30% by Fenton's reagent (FR), a powerful source of OH. radicals. Likewise, the uptake of glutamic acid, leucine and arginine was diminished. The mediated diffusion of 6-deoxy-D-glucose was not affected. The H+ symport of maltose and trehalose was inhibited by some 40% both in the initial rate and in the accumulation ratio. FR had a dramatic inhibitory effect when present during preincubation with 50 mmol/L glucose. In the obligately aerobic Lodderomyces elongisporus the uptake of all amino acids tested was decreased by 15-30%, that of 6-deoxy-D-glucose by about 10%. The initial rates of uptake of maltose and trehalose were depressed by FR by 40% and the acceleration of uptake observed after 8 min of incubation, was abolished by FR completely. Acidification rate of the external medium by S. cerevisiae in the presence of glucose or galactose was enhanced three-fold, that after subsequently added K+ was substantially decreased. FR appears to have a dual effect on sugar and amino acid transport processes in yeast: (1) it blocks carrier protein synthesis; (2) it inhibits the source of energy for transport. It does not appreciably affect the carrier proteins themselves.
Keywords: aminokyseliny; Saccharomycetales; aktivní transport; železo; Saccharomyces cerevisiae; Fungal Proteins; Hydrogen-Ion Concentration; peroxid vodíku; Hydrogen Peroxide; Biological Transport, Active; koncentrace vodíkových iontů; Carrier Proteins; kinetika; Iron; metabolismus sacharidů; Carbohydrate Metabolism; fungální proteiny; Kinetics; transportní proteiny; Amino Acids